Measuring people's views on health system performance: design and development of the People's Voice Survey - Lewis, TP; Kapoor, NR; Aryal, A; Bazua-Lobato, R; Carai, S; Clarke-Deelder, E; Croke, K; Dayalu, R; Espinoza-Pajuelo, L; Fink, G; Garcia, PJ; Garcia-Elorrio, E; et al. (Public Library of Science, 2023)
Todd Lewis and co-authors discuss development and use of the People's Voice Survey for health system assessment.